2012
DOI: 10.1210/en.2012-1375
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Fever Depends on Prostaglandin E2 Production Specifically in Brain Endothelial Cells

Abstract: Immune-induced prostaglandin E2 (PGE2) synthesis is critical for fever and other centrally elicited disease symptoms. The production of PGE2 depends on cyclooxygenase-2 and microsomal prostaglandin E synthase-1 (mPGES-1), but the identity of the cells involved has been a matter of controversy. We generated mice expressing mPGES-1 either in cells of hematopoietic or nonhematopoietic origin. Mice lacking mPGES-1 in hematopoietic cells displayed an intact febrile response to lipopolysaccharide, associated with el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 46 publications
15
99
1
2
Order By: Relevance
“…PGE 2 is considered as a major pyrogenic mediator of fever (Engstrom et al, 2012;Matsumura et al, 1998;Yamagata et al, 2001). The role of PGE 2 in induction of fever in mammals was already reported in 1971 by Milton and Wendlandt (1971) who demonstrated that microinjection of PGE 2 into the third ventricle of conscious cats and rabbits cause a rise of body temperature.…”
Section: The Key Role Of Pgementioning
confidence: 91%
“…PGE 2 is considered as a major pyrogenic mediator of fever (Engstrom et al, 2012;Matsumura et al, 1998;Yamagata et al, 2001). The role of PGE 2 in induction of fever in mammals was already reported in 1971 by Milton and Wendlandt (1971) who demonstrated that microinjection of PGE 2 into the third ventricle of conscious cats and rabbits cause a rise of body temperature.…”
Section: The Key Role Of Pgementioning
confidence: 91%
“…Approximately 24 h after irradiation, the animals were injected i.v. with 2 x 10 6 freshly prepared GFP + CD45 + bone marrow cells, as described in detail elsewhere (Engström et al, 2012). After the injection, mice were immediately transferred to an isolated room with autoclaved cages Matsuwaki et al,p.…”
Section: Irradiation and Bone Marrow Transplantationmentioning
confidence: 99%
“…The proinflammatory cytokine interleukin-1β (IL-1β) has been shown to be an important mediator of the immune-induced glucocorticoid release (Berkenbosch et al, 1987;Besedovsky et al, 1986) , but the signaling pathway by which IL-1β exerts this function has not been determined. While there is a strong evidence that brain endothelial cells, by induced prostaglandin (PG) synthesis, are critical for the immune-elicited fever (Engström et al, 2012), it has been suggested that perivascular macrophages, located within the two sheets of the basal membrane of the cerebral blood vessels and hence on the abluminal side of the endothelial cells, mediate IL-1β evoked HPA-axis activation, also by induced PGsynthesis Sawchenko, 2002, 2003;Serrats et al, 2010). Deletion of the gene encoding microsomal prostaglandin E-synthase (Trebino et al, 2003), rending the animals unable to elicit central PGE2 synthesis upon immune stimulation (Engblom et al, 2003), results in attenuated corticosterone release to such stimuli (Elander et al, 2009), showing an important role for immune-induced PGE2 in this response.…”
Section: Introductionmentioning
confidence: 99%
“…They found similar expression of these markers in all three groups of mice and concluded that the innate immune response of chimeric mice is similar to that of WT mice (Turrin et al, 2007). Furthermore, in a previous study (Engstrom et al, 2012) we demonstrated that although the irradiation and transplantation, similar to what was seen in the present study, resulted in a major replacement of brain perivascular cells the fever response of WT→WT and KO→KO mice was similar to that of non-irradiated WT and KO mice, respectively, suggesting that the irradiation procedure per se did not affect the fever response. The same observation was obtained in the present study, and while it does not exclude that the irradiation procedure could have influenced peripheral and central IL-6 levels in the chimeric mice, it seems unlikely that any such changes would have significantly influenced the febrile responses in these mice.…”
Section: Discussionmentioning
confidence: 76%
“…Recent work from this laboratory has suggested that hematopoietic cells and plasma PGE 2 are not contributing to the fever signaling. Instead, the endothelial cells in the brain were identified as the main source of PGE 2 important for the fever generation (Engstrom et al, 2012). While IL-6 by itself does not elicit PGE 2 synthesis, it is possible that the febrile response never-the-less could be dependent on IL-6 signaling via brain endothelial cells, through a yet unidentified mechanism (Nilsberth et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%